Obscuring effect of coding developmental disability as the underlying cause of death on mortality trends for adults with developmental disability: a cross-sectional study using US Mortality Data from 2012 to 2016 - Landes, Scott D; Stevens, James Dalton; Turk, Margaret A (BMJ open, 2019)
ObjectiveTo determine whether coding a developmental disability as the underlying cause of death obscures mortality trends of adults with developmental disability.DesignNational Vital Statistics System 2012–2016 US Multiple Cause-of-Death Mortality files.SettingUSA.ParticipantsAdults with a developmental disability indicated on their death certificate aged 18 through 103 at the time of death. The study population included 33 154 adults who died between 1 January 2012 and 31 December 2016.Primary outcome and measuresDecedents with a developmental disability coded as the underlying cause of death on the death certificate were identified using the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision code for intellectual disability, cerebral palsy, Down syndrome or other developmental disability. Death certificates that coded a developmental disability as the underlying cause of death were revised using a sequential underlying cause of death revision process.ResultsThere were 33 154 decedents with developmental disability: 7901 with intellectual disability, 11 895 with cerebral palsy, 9114 with Down syndrome, 2479 with other developmental disabilities and 1765 with multiple developmental disabilities. Among all decedents, 48.5% had a developmental disability coded as the underlying cause of death, obscuring higher rates of choking deaths among all decedents and dementia and Alzheimer’s disease among decedents with Down syndrome.ConclusionDeath certificates that recorded the developmental disability in Part I of the death certificate were more likely to code disability as the underlying cause of death. While revising these death certificates provides a short-term corrective to mortality trends for this population, the severity and extent of this problem warrants a long-term change involving more precise instructions to record developmental disabilities only in Part II of the death certificate.